2020
DOI: 10.1007/s12144-020-00614-6
|View full text |Cite
|
Sign up to set email alerts
|

Career success in the University setting: Examining the role of narcissism facets

Abstract: The purpose of this research is to examine the association of narcissism facets with subjective and objective career success, as well as the impact of the professional field. Data from 282 employees of a German universityboth scientists and administrative staffwho completed an online survey were analysed. Results showed a significant negative relationship between vulnerable narcissism and career success. The associations of the grandiose narcissism subfacets: grandiose exhibitionism and entitlement/ exploitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
(102 reference statements)
1
5
0
Order By: Relevance
“…Our results contradict previous studies that highlight the negative repercussions of this organizational behaviour on publications . On the contrary, our study corroborates the incipient empirical evidence that recently began to reveal the positive effects of narcissism on the quantity and quality of publications (Oflu et al, 2020;Posada-Arias et al, 2018). This being the case, our work provides a perspective that allows for a broader view when evaluating the actual extent of the impact of organizational narcissism on knowledge sharing among academics, which is not only limited to the publication dimension.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our results contradict previous studies that highlight the negative repercussions of this organizational behaviour on publications . On the contrary, our study corroborates the incipient empirical evidence that recently began to reveal the positive effects of narcissism on the quantity and quality of publications (Oflu et al, 2020;Posada-Arias et al, 2018). This being the case, our work provides a perspective that allows for a broader view when evaluating the actual extent of the impact of organizational narcissism on knowledge sharing among academics, which is not only limited to the publication dimension.…”
Section: Discussionsupporting
confidence: 86%
“…participation in external academic networks. In contrast, narcissism impacts to a lesser extent on the written contributions that are usually an activity developed in the short and medium term; regarding this result in particular, there are coincidences with previous works (Oflu et al, 2020;Posada-Arias et al, 2018). However, this result can be examined more broadly and in the light of the current demands for academics, from whom good results are expected not only in terms of publications but also in teaching, entrepreneurship or commercialization of research results (Araujo et al, 2020).…”
Section: Knowledge Sharing Among Academicsmentioning
confidence: 75%
See 1 more Smart Citation
“…On professional and occupation front also, a desire for skill demonstration and work admiration in higher education and specific profession have been linked to narcissism. (Jauk and Sordia, 2018;Oflu, C., Baluku, M. M., & Otto, K. 2020). Our study reports higher narcissism in post graduate subjects and persons pursuing a specific profession.…”
Section: Results and Discusssionmentioning
confidence: 99%
“…Recent literature explores dark personality aspects in organisations, ( Schyns et al, 2019 ; Czarna and Zajas, 2020 ; Ray et al, 2020 ), career success ( Oflu et al, 2020 ) and leadership ( Van Scotter, 2019 ; Mackey et al, 2020 ; Syed et al, 2020 ). Spurk et al (2016) observed that narcissism as a dark personality trait is positively related to salary, Machiavellianism is positively related to leadership position, and career satisfaction while psychopathy is negatively related to career outcomes.…”
Section: Introductionmentioning
confidence: 99%